THE EFFECT OF EXTENSIVE READING TOWARDS STUDENTS’ VOCABULARY MASTERY - Delvia Buana; Widya Syafitri (Universitas Pahlawan Tuanku Tambusai, 2021)
In this study researcher found some problems that faced by students of grade X in MAS TI Koto Tinggi. The problems were: first, Students did not understand the meaning of vocabulary in the reading text. Secondly, Students seemed to have lack of willingness and interest in learning English. Thirdly, Students’ ability in English was still average especially in vocabulary and grammar. The study aimed: (1) To find out whether there is a significant effect of using extensive reading towards students’ vocabulary mastery, (2) To find out whether there is a significant difference of students who are using extensive reading and students who are not using extensive reading, (3) To know whether students’ reading taught by using extensive reading is better than students who are not taught by it. The class research was consisted of two classes and the students are 24 students. the first was experiment class with 12 students and the second was control class with 12 students. The researcher did pre-test in both class, then the researcher gave treatment in experiment class by using extensive reading method then did post-test in both class to know the result. Data that has been collected was processed by using SPSS. 20 The results showed that most of the average score of pre-test in experiment class 55.67. The average score of post-test in experiment class was 81. That was mean that the class category of student’s vocabulary mastery in reading skill after did treatment by using extensive method was increase. The average score of pre -test in control class was 58.67, then the average of post-test in control class was 66.67. it’s mean that the class category of student’s vocabulary mastery in reading skill after taught by using conventional method was increase in score, but the category was still in fair category.